EFFECT OF GROWTH RETARDANTS ON THE VEGETATIVE GROWTH, FLOWERING AND YIELD OF HELICONIA (HELICONIA PSITTACORUM) VAR. RED TORCH UNDER 50 PER CENT SHADE NET CONDITION - SHEETALBEN K. JADHAV,; S. L. CHAWLA,; ROSHNI AGNIHOTRI,; R. A. GURJAR, (The Bioscan, 2015)
An investigation was carried out to study the effect of plant growth retardants on the growth, flowering and yield of heliconia (Heliconia psittacorum) var. Red Torch under 50 per cent green shade net condition during 2012- 2013. The experimental results revealed that among all growth retardants, paclobutrazol @ 300 ppm drastically suppressed plant height (24.86 cm, 25.95 cm, 27.20 cm and 49.60 cm) at 3, 6, 9 and 12 MAP, respectively and it was at par with 150 ppm paclobutrazol and followed by TIBA @ 30 ppm. Other vegetative parameters like leaves per plant (4.60, 6.20, 4.66 and 4.33 at 3, 6, 9 and 12 MAP, respectively), sucker per clump (6.13, 12.20 and 15.86 at 6, 9 and 12 MAP, respectively) and leaf area (477.73 cm 2 at 12 MAP) were found maximum in MH @ 50 ppm. Minimum days to flowering (147.20), maximum flowering duration (55.40 days), number of bracts and florets (4.60 and 12.06, respectively), rachis and stalk length (15.41 cm and 110.98 cm, respectively), spikes per clump (4.46) and vase life (13.33 days) was also found in the same treatment. It can be concluded that MH @ 50 ppm proved to be the best treatment for obtaining higher yield of good quality flowers